(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. Studies on physical activity, which is positively associated with physical fitness, reveal that children’s activity is not sufficient (BHFNC, 2010; Chen, Zheng, Yi, & Yao, 2014; Currie et al., 2012), and their physical fitness deteriorates (Volbekienė & Kavaliauskas, 2002; Мирошниченко & Астраханцев, 2005; Синявский, Власов, & Сергеев, 2009). Non-formal physical education (NFPE) is one of the means to increase children’s physical activity and physical fitness. The aim of this study was to determine the influence of NFPE on the physical fitness of 6th grade pupils. Methods. The research was conducted in May, 2013; 356 six-graders (48.0% of girls) from four Klaipėda city comprehensive schools participated in the research. As many as 56.5% of children (48.3% of girls) participated in NFPE in school and out of school. The participants completed five physical fitness tests. Results. Independent t test revealed that the results of boys who attended the NFPE group of cardiorespiratory fitness, t(180) = −2.093, p = .038; upper body muscular strength and endurance, t(182) = 2.413, p = .017; abdominal muscular strength and endurance, t(186) = 3.282, p = .001; explosive leg power, t(183) = 1.967, p = .049, and girls’ results of abdominal muscular strength and endurance, t(172) = 2.687, p = .008 were significantly higher than those in the NFPE non attended group. Conclusion. Non-formal physical education is a meaningful educational form for increasing children’s, particularly boys’, health related physical fitness; therefore it is purposeful to encourage children to participate in physical activities in school and after classes. Keywords: non-formal physical education, physical fitness, testing.